KINERJA SOSIAL LEMBAGA KEUANGAN MIKRO AGRIBISNIS (LKM-A) DI KECAMATAN DAWE, KABUPATEN KUDUS - Mahsufah, Maqsul; Gayatri, Siwi; Dalmiyatun, Tutik (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 13 No 3 (2019): Vol. 13, No. 3, 2019, 2019)
Agriculture Ministry through the Rural Agribusiness Development (PUAP)  program was expected to reduce poverty and unemployment in rural areas by developing Microfinances Agribusiness Institution (LKM-A). LKM-A has a purpose to help farmers in rural areas to obtain capital resource for their agribusiness. However, the implementasion of LKM-A still not developed optimally. The research on the social performance of LKM-A were aims to analyze social performance, to analyze revenue generating of LKM-A and to analyze the relationship between social performance and revenue generating of LKM-A in Dawe District, Kudus Regency. This research was conducted in February 12th – April 5th, 2018 in Dawe District, Kudus Regency. Survey method was used in this research. 18 LKM-A was choosen as population in this research. The data was analyzed by Spearman correlation. Social performance was analyzed using MIX Market Social Performance Standards with 16 indicators. The result shows that only 3 indicators were in medium category (0 – 50%), namely capital resources, the ratio of female debtors and the ratio low income debtors. The revenue generating was not in developed category. Based on statistical analysis, there was not significant influence between social performance and revenue generating